Investigation of feedstock on compost characteristics - Tong, Jun Yong. (2010)
Biodegradable organics waste occupies a large proportion of the total waste generated in a household. The use of earthworms to degrade such waste is gaining popularity for its ability to produce valuable soil amendment at a shorter time compared to composting. In this study, five different feedstock are subjected to composting, vermicomposting and combined system respectively to determine the effect on the characteristics of vermicompost and compost. Physical and chemical analysis such as volatile solids, pH, moisture content, N:P:K ratio and electrical conductivity are conducted to compare the differences. Balsam plants are used to demonstrate the reduction in the flowering time when the soil is amended with the produced compost and vermicompost.